The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1097/sap.0000000000003183
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Benefit Analysis of Osseointegrated Prostheses for Lower Limb Amputees in the US Health Care System

Abstract: Background Patients with transfemoral and transtibial amputations generally rely on socket-suspended (SS) prostheses for ambulation. The use of these aids can be complicated by poor fit, leading to tissue damage, pain at the socket-limb interface, and inability to ambulate. Osseointegrated implants (OIs) directly anchor a prosthesis to the patient’s residual limb, eliminating these issues. However, they require customized components and additional surgeries. The purpose of this study was to conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 23 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Osseointegrated implants also shift weight-bearing directly to the skeletal system, rather than the soft tissue stump, providing heightened proprioception and decreasing the metabolic demand of movement 5–7 . In addition to circumventing many of the risks associated with SS prostheses, OIs provide a higher quality of life and are cost-effective when compared with poorly tolerated SS protheses 8–10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Osseointegrated implants also shift weight-bearing directly to the skeletal system, rather than the soft tissue stump, providing heightened proprioception and decreasing the metabolic demand of movement 5–7 . In addition to circumventing many of the risks associated with SS prostheses, OIs provide a higher quality of life and are cost-effective when compared with poorly tolerated SS protheses 8–10 …”
mentioning
confidence: 99%
“…[5][6][7] In addition to circumventing many of the risks associated with SS prostheses, OIs provide a higher quality of life and are cost-effective when compared with poorly tolerated SS protheses. [8][9][10] Ideal candidates for lower limb osseointegration have mature bone stock and no active infection or history of poor wound healing. 11 At our institution, a team-based approach to single-stage implantation is used.…”
mentioning
confidence: 99%
“…9,10 In patients with poorly tolerated socket prostheses, OI prostheses have been shown to lead to better patient-reported outcomes, including more prosthesis use, improved mobility, and higher health-related quality of life (HRQoL). 11,12 Osseointegration prostheses also allow for a more normal gait and improved sensory feedback due to vibration transduction and skeletal proprioception. [13][14][15] Surgical site infections (SSIs) have a prevalence of over 20% in orthopedic surgeries, and hardware implantation has been shown to increase this risk.…”
mentioning
confidence: 99%
“…In fact, the improvements in quality of life outweigh the added costs of custom implants and additional surgeries, as shown in U.S.-based economic analyses of osseointegrated implantation 20,21 . Those authors concluded that osseointegrated implantation outperformed traditional socket-based prostheses in the long term, particularly among patients requiring replacement prostheses or revision surgeries due to poor socket tolerance 20,21 . Given the longitudinal enhancement in device ergonomics as well as reductions in perioperative complications, interest in and access to osseointegrated technologies are poised to grow.…”
mentioning
confidence: 99%
“…In addition to the clinical improvements that osseointegrated prostheses have made in patients’ lives, the procedure has been demonstrated to be cost-effective. In fact, the improvements in quality of life outweigh the added costs of custom implants and additional surgeries, as shown in U.S.-based economic analyses of osseointegrated implantation 20,21 . Those authors concluded that osseointegrated implantation outperformed traditional socket-based prostheses in the long term, particularly among patients requiring replacement prostheses or revision surgeries due to poor socket tolerance 20,21 .…”
mentioning
confidence: 99%